The effect of real-time PCR as a part of diagnostic procedure on the efficacy of treatment of multiple drug resistant tuberculosis - L. V. Petrova; E. V. Sevastyanova; A. M. Vasilieva; E. A. Kuklina; Yu. A. Soloviev; L. N. Chernousova (Туберкулез и болезни лёгких)
The objective of the study: to investigate the eﬀect of the molecular genetic test of PCR-RT within the procedure of microbiological diagnosis of tuberculosis on the eﬃcacy of chemotherapy in patients with multiple drug resistant tuberculosis in the Mary-El Republic.Subjects and methods. 344 patients with multiple drug resistant tuberculosis were enrolled in the study. The eﬃcacy of chemotherapy was assessed based on sputum conversion conﬁrmed by culture.Results. It was demonstrated that PCR-RT for determining mutations in the diagnostic material samples associated with drug resistance to rifampicin, isoniazid, and ﬂuoroquinolones, and the early prescription of an adequate chemotherapy regimen based on this study, followed by amendment of the treatment regimen according to the results of phenotypic drug susceptibility tests, signiﬁcantly (on average from 3.6 to 2.5 months, p <0.05) reduced the time required for sputum conversion conﬁrmed by culture, which reduced the time of in-patient treatment.